The Predictive Role of Lymphocyte-to-Monocyte Ratio in Acute Kidney Injury in Acute Debakey Type I Aortic Dissection - Ma, Xiaochun; Chen, Shanghao; Yun, Yan; Zhao, Diming; Li, Jinzhang; Wu, Zezhong; Liu, Yanwu; Shen, Hechen; Ma, Huibo; Wang, Zhengjun; Zou, Chengwei; Zhang, Haizhou (Frontiers in Surgery, 2021)
Abstract Background. The postoperative acute kidney injury (AKI) represents a common complication in the Acute Debakey Type I Aortic Dissection (ADTIAD) and predicts a poorer prognosis. The clinical evidence is scarce supporting the predictive value of the preoperative lymphocyte-to-monocyte ratio (LMR) in postoperative AKI in ADTIAD. Methods. In this retrospective cohort study, 190 consecutive patients with ADTIAD enrolled for surgical treatment between January 1, 2013, and December 31, 2018. The diagnosis of AKI followed the Kidney Disease: Improving Global Outcomes guidelines (KDIGO). Preoperative LMR and other possible risk factors were analyzed for their prognostic value in the postoperative AKI in ADTIAD. Results. The subjects were assigned to the low-LMR and high-LMR groups according to the median value of preoperative LMR. For postoperative AKI, the incidence and the severity in the low-LMR group were statistically different from that of the high-LMR group. Besides, the lower LMR was statistically associated with the more extended ICU stay and intubation time and higher incidences of ischemic stroke and in-hospital mortality. Additionally, in the multivariable analysis, the preoperative LMR was an independent predictor for postoperative AKI in ADTIAD. A predictive model for postoperative AKI in ADTIAD was established incorporating LMR. Conclusions. LMR is an independent prognostic indicator incorporated into the predictive model with other risk factors to predict the postoperative AKI in ADTIAD.